Transcatheter closure of patent vertical vein after repair of total anomalous pulmonary venous connection - Verma, Sudeep (Ann Pediatr Cardiol, 2015)
BACKGROUND: Vertical vein is left patent in some cases of supra-cardiac total anomalous pulmonary venous connection (TAPVC) when there is hemodynamic instability due to noncompliant left atrium and ventricle. After the peri-operative period, this results in features of pre-tricuspid shunt. MATERIALS AND METHODS: Three cases with patent vertical vein following repair of supra-cardiac TAPVC presented with features of pre-tricuspid shunt on follow-up. Trans-catheter closure of patent vertical vein was performed using vascular plug in all three subjects. RESULTS: The procedure was technically successful in all the patients. There was a complication related to catheter tip breakage in one of them, which was successfully managed. There was no impingement on pulmonary vein in any of the patients. CONCLUSION: Patent vertical vein following TAPVC repair results in features of pre-tricuspid shunt. Transcatheter closure of the patent vein is feasible.